A/D converter trends: Power dissipation, scaling and digitally assisted architectures - Murmann, B. (2008 IEEE Custom Integrated Circuits Conference, 2008)
This paper summarizes recent trends in the area of low-power A/D conversion. Survey data collected over the past eleven years indicates that the power efficiency of ADCs has improved on average by a factor of two every two years. A closer inspection on the impact of technology scaling is presented to explain the observed trend in the context of shrinking supply voltages and increasing device speed. Finally, a discussion on minimalistic and digitally assisted design approaches is used to sketch a route toward further improvements in ADC power efficiency and performance.